2015
DOI: 10.1037/hea0000196
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality and the recovery of quality of life following hematopoietic stem cell transplantation.

Abstract: Objective Spirituality has been linked to improved adjustment and functioning in individuals with cancer; however, its effect on quality of life following hematopoietic stem cell transplantation (HSCT) has not been well-studied. This study investigated changes in spirituality in hematologic cancer patients recovering from HSCT and relationships between spirituality and dimensions of quality of life following HSCT. Methods Participants (N = 220) completed measures of two dimensions of spirituality (meaning/pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…We developed a psychological intervention tailored for Chinese rural PLHIV that effectively enhanced their resilience, psychosocial well-being, and quality of life (Yu et al, 2014). Although the resilience research has documented affective, cognitive, and behavioral concomitants (Mak, Ng, & Wong, 2011;Tugade & Fredrickson, 2004), little has been investigated about spiritual belief (Klasen et al, 2010;Leeson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We developed a psychological intervention tailored for Chinese rural PLHIV that effectively enhanced their resilience, psychosocial well-being, and quality of life (Yu et al, 2014). Although the resilience research has documented affective, cognitive, and behavioral concomitants (Mak, Ng, & Wong, 2011;Tugade & Fredrickson, 2004), little has been investigated about spiritual belief (Klasen et al, 2010;Leeson et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few longitudinal studies assessing R/S with the FACIT‐Sp in patients with cancer . In addition, a number of studies have measured SWB with the FACIT‐Sp over time as an outcome following some type of psychosocial intervention .…”
Section: Introductionmentioning
confidence: 99%
“…There have been a few longitudinal studies assessing R/S with the FACIT-Sp in patients with cancer. [20][21][22][23][24][25][26] In addition, a number of studies have measured SWB with the FACIT-Sp over time as an outcome following some type of psychosocial intervention. [27][28][29][30][31][32][33] Generally, higher scores on the FACIT-Sp have been predictive of or associated with better HRQOL; however, no clear patterns of change in Meaning, Peace, and Faith over time are apparent.…”
Section: Introductionmentioning
confidence: 99%
“…A national survey in the United States indicates that patients with cancer report an increased role of spirituality and religion in their lives between prediagnosis and a median of 10 years postdiagnosis . Change in a sense of meaning/peace has been related to decreased depression over time in breast cancer patients after diagnosis and in hematopoetic cancer patients after stem cell transplantation . Another study of cancer patients about 3.5 years after diagnosis showed that greater changes in a sense of meaning/peace measured over 1 year were associated with better mental health and lower distress at follow‐up, while faith was only related to perceived growth .…”
Section: Introductionmentioning
confidence: 99%
“…12 Change in a sense of meaning/peace has been related to decreased depression over time in breast cancer patients after diagnosis and in hematopoetic cancer patients after stem cell transplantation. 13,14 Another study of cancer patients about 3.5 years after diagnosis showed that greater changes in a sense of meaning/peace measured over 1 year were associated with better mental health and lower distress at follow-up, while faith was only related to perceived growth. 15 No studies have examined differential effects of changes in meaning versus peace with respect to their effects on mood.…”
Section: Introductionmentioning
confidence: 99%